TOTAL ANKLE REPLACEMENT FOR TREATMENT OF AVASCULAR NECROSIS OF THE TALUS - Tan, Jin Aun; Bajuri, Mohd Yazid; Leong, Juzaily Fekry; Kb, Levin; Alias, Azammuddin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Avascular necrosis (AVN) of talus is a well-known complication following talar neck fracture that leads to osteoarthritis of the ankle joint. Tibiotalar fusion is the gold standard of treatment in end-stage ankle osteoarthritis with predictable good outcome. With the introduction of newer generation of total ankle replacement (TAR), it is gaining popularity as an alternative treatment in selected cases of ankle joint osteoarthritis secondary to AVN talus. We present here a case of ankle joint osteoarthritis secondary to AVN talus in a 30-year-old female in which a TAR was performed. We wish to highlight that TAR can be done in ankle joint osteoarthritis with AVN talus in properly selected cases.